O tratamento crônico com fluoxetina reverte os efeitos nociceptivo e antinociceptivo induzidos pela ativação dos receptores 5-HT1A e 5-HT2C da amídala de camundongos confinados aos braços do labirinto em cruz elevado - Furuya-da-Cunha, Elke Mayumi (Universidade Federal de São Carlos, 2019)
Several studies indicate that anxiety and depression may be accompanied by symptoms of severe pain with no precise location or apparent lesions. Several evidences demonstrate that some antidepressive drugs used in the treatment of these emotional disorders are also effective in the relief of pain. The interaction between emotional and sensorial responses is of high relevance for the survival of the species. Several studies have shown that exposure to threatening situations results in behavioral and physiological defense reactions that be accompanied by inhibition of pain. The amygdala, a subcortical nucleus complex, has been shown to be involved in the mechanism of fear-induced antinociception. And it being a complex of interface between the sensorial and emotional stimuli. Evidences have shown that stimulation of this structure can induce fear or anxiety reactions, accompanied by analgesia, thus suggesting its participation in the defense system and nociception modulation.The elevated plus maze (EPM) is an apparatus used to assess rodent anxiety and it is sensitive to anxiolytic and anxiogenic effect of drugs. In this sense, EPM is used to study the neurobiology of antinociception induced by the aversive potential of the open arms experiment. Thus, considering evidences of the antiaversive role of serotonin in the amygdala, observed with chronic treatment with serotonin reuptake inhibitors, this study aimed to evaluate the role of amygdala 5-HT1A and 5-HT2C serotonin receptor subtypes on nociception and antinociception effects of mice exposed to the EPM in this context. For this, 5-HT1A (8-OH-DPAT) and 5-HT2C (MK-212) receptor agonists were microinjected intra-amygdala associated with chronic systemic treatment of fluoxetine in mice. The animals were confined in the enclosed or open arm of the EPM and the number of abdominal writings after the intraperitoneal (i.p.) injection of acetic acid solution was counted. Intra-amygdala treatment with 8-OH-DPAT produced an increase in the number of writhes in both mice that were confined in the open arm and those that were confined in the enclosed arm. However, treatment fluoxetine + 8-OH-DPAT blocked the effect of intra-amygdala injection only for the mice confined in the open arm. Intra-amygdala treatment with MK-212 produced a decrease in the number of writhes only in mice that were confined to the open arm, and the fluoxetine + MK-212 treatment impaired this effect. These results suggest that chronic treatment with fluoxetine reversed the effects produced by the activation of the 5-HT1A and 5-HT2C receptors in the amygdala of mice confined to the EPM.
Chronic fluoxetine treatment reverse nociceptive and antinociceptive effects induced by activation of the 5-HT1A and 5-HT2C amygdala receptors of confined mice to elevated plus maze
Keywords: Antinocicepção; Labirinto em cruz elevado; Serotonina; Fluoxetina; Amidala; Camundongos; Antinociception; Elevated plus maze; Serotonin; Fluoxetine; Amygdala; Mice; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::NEUROFISIOLOGIA